Corporate Responses to HIV/AIDS : Case Studies from India - World Bank (Washington, DC : World Bank, 2012)
This collection of case studies aims to contribute to the growing evidence on private sector engagement in the fight against HIV and AIDS and the challenges businesses are overcoming in this fight. By capturing the experiences of the local private sector, it seeks to foster a more active response from the business community and to encourage new partnership approaches from government, civil society, and development organizations to leverage the goodwill and competencies of the private sector. In a country as large as India, more active engagement of the private sector is critical to achieve the scale of intervention needed to get ahead of HIV and AIDS. The case studies illustrate the importance of integrating multiple stakeholders in the fight against HIV and AIDS. They also highlight the growing investment of businesses in that fight-an investment that recognizes their vulnerability to the economic and social impact of the epidemic. And they show what businesses can achieve by tackling HIV and AIDS through the workforce. By showcasing their achievements and illuminating the lessons of their experience, these case studies seek to convince other businesses that taking part in the fight against HIV and AIDS is both within their reach and in their interest.